Influence of intrinsic and institutional factors on relationship between attitude and sustainable behaviours among Malaysian urban population - Yoong, Siew Wai (2018)
Empirical investigations justify that pro-environmental behaviour is functions of attitude, capabilities, and the presence of environmental factors. Hitherto, there is a lack of encouraging evidence concomitant by consumer to adopt environmentally friendly products and services. The social cognitive theory undergirds for this study. The theory acknowledges the interdependency and reciprocal relationship between an individual and the situation. The rationale for the theoretical framework is to understand and characterise significant intrinsic and institutional factors in constructing attitude and behaviour relationship, and subsequently spur sustainable behaviour adoption. Non-probability quota sampling method with structured questionnaire were employed. The survey captured responses from 500 Malaysians of 18 years and above, across five geographical regions. The Partial Least Square-Structural Equation Modelling (PLS-SEM) was used to examine the hypothesised relationships. This study enriches the existing knowledge on pro-environmental behaviour adoption by expanding on sustainable behaviour as the total summation of the recycle, reuse, and reduce behaviours. The results posit that in the private setting, attitude functions (utilitarian, ego-defensive, and experiential-schematic, except for social-adjustive), together with perceived self-efficacy, have a direct influence on attitude formation. In addition, evidence from this study suggests a direct influence of perceived self-efficacy on behaviour among higher sustainable behaviour adopters. This study also finds that institutional forces encompass coercive, normative, and mimetic forces, have a direct influence on sustainable behaviour. However, present study does not have sufficient evidence to support mediating effects of value-expressive function and social capital on the relationship between associated attitude and behaviour, institutional forces and sustainable behaviour respectively. Furthermore, social capital is negatively correlated with behaviour among low sustainable behaviour adopters. Marketers can frame their communication campaign premise on lifestyle-based sustainable behaviour, with attitude functions and perceived self-efficacy as the content strategy to maintain and defend both attitude and sustainable behaviour. The findings speaks for the importance of collaboration among institutional forces to intensify social capital to contextualise the adoption of sustainable behaviour. Future research can examine the antecedence for perceived self-efficacy and explore other social psychological variables in maintaining and sustaining the relationship between attitude and sustainable behaviour.